Science and News - Tara Tobin Cataldo; Kailey Langer; Amy G Buhler; Samuel R Putnam; Rachael Elrod; Ixchel M Faniel; Lynn Silipigni Connaway; Christopher Cyr; Brittany Brannon; Joyce Kasman Valenza; Erin M Hood; Randy A Graff (Issues in Science and Technology Librarianship, 2019)
This paper explores how students judge scientific news resources, as they might find through a Google search. The data were collected as part of an Institute of Museum and Library Services (IMLS) funded project. Students used a simulated search engine that ensured study participants found the same search results while seeking information for a science-related school project. The 116 students from high school, community college, undergraduate, and graduate communities evaluated three online news resources for their helpfulness, citability, credibility, and container. Analysis of quantitative data from the study indicated that students may find news resources helpful for a science project, but do not always consider them citable. Students appeared to focus on the organization that produced the news resource (i.e., source) when judging its credibility. Not all students identified the resources’ containers as news, even when the source was widely known. The researchers note differences in judgment between educational stages. Differences were especially pronounced between high school and higher education students, with high school students more likely to find news sources worthy of citing for school projects.